Model testing of an oscillating water column spar-buoy wave energy converter isolated and in array: Motions and mooring forces. (1st October 2016) - Correia da Fonseca, F.X.; Gomes, R.P.F.; Henriques, J.C.C.; Gato, L.M.C.; Falcão, A.F.O.
Abstract: For large-scale exploitation of the offshore wave energy resource, floating wave energy converters should be deployed in arrays with inter-body mooring connections, reducing the number of bottom slack-mooring lines needed and consequently the project total cost. The present paper concerns the experimental investigation of the dynamics, energy extraction and mooring system performance of the OWC spar-buoy, deployed isolated and in a triangular array configuration, with inter-body mooring connections. For this purpose, three 1:32 scale models of the device were built and tested at Plymouth University large ocean basin. Pressure variations inside the OWC air chamber, mooring line forces in the buoy fairleads and buoys motion were measured. The turbine damping effect was simulated using a calibrated orifice fixed at the top of the air chamber. Tests were carried out for regular and irregular wave conditions with different wave heights and periods. Several model configurations were tested, including the variation of the mooring lines pre-tension, the structure ballast and the turbine damping. The closure of the air chamber, for turbine protection purposes, was found to be correlated with a large increase of the mooring loads. Results show a comparable performance between the three-device array and isolated device configuration. Highlights: Three OWC spar-buoy 1:32nd scale models were tested in a wave tank. The devices were tested isolated and in array, under regular and irregular waves. The motion, energy extraction and mooring system performances were studied. Comparable power performances were found between array and isolated device scenario. Closing the air chamber for turbine protection aggravated the loads on the moorings.